2023
DOI: 10.1159/000533692
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Pattern in Somatotroph Pituitary Neuroendocrine Tumors

Paulina Kober,
Julia Rymuza,
Szymon Baluszek
et al.

Abstract: <b><i>Introduction:</i></b> Growth hormone secretion by sporadic somatotroph neuroendocrine pituitary tumors (PitNETs) is a major cause of acromegaly. These tumors are relatively heterogenous in terms of histopathological and molecular features. Our previous transcriptomic profiling of somatotroph tumors revealed three distinct molecular subtypes. This study aimed to investigate the difference in DNA methylation patterns in subtypes of somatotroph PitNETs and its role in distinctive gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Integrated methylation data consensus cluster analysis confirmed that somatotroph tumors separate into three distinct epigenomic subclusters, as recently described (Fig. 3 a) [ 11 ]. SF1 expression depicted by immunoreactivity (this study) and RNA expression levels (external studies) demonstrated that the three epigenomic subclusters relate to the tumors denoted as DGST-PIT1/SF1, DGST-PIT1 and SGST-PIT1 in this study.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Integrated methylation data consensus cluster analysis confirmed that somatotroph tumors separate into three distinct epigenomic subclusters, as recently described (Fig. 3 a) [ 11 ]. SF1 expression depicted by immunoreactivity (this study) and RNA expression levels (external studies) demonstrated that the three epigenomic subclusters relate to the tumors denoted as DGST-PIT1/SF1, DGST-PIT1 and SGST-PIT1 in this study.…”
Section: Resultssupporting
confidence: 83%
“…The methylation data of our 31 in-house samples were integrated into a large reference series of 77 somatotroph PitNETs compiled from three independent publicly available datasets [ 11 , 17 , 23 ]. Integrated methylation data consensus cluster analysis confirmed that somatotroph tumors separate into three distinct epigenomic subclusters, as recently described (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations